Improving survival and limiting toxicity: latest advances in treating human epidermal growth factor receptor 2 overexpressing breast cancer - Abramson, Vandana G. (SAGE Publications, 2012)
In recent years, new strategies for the treatment of breast cancer have focused on extensive target identification and understanding the expression, regulation and function of critical signaling pathways involved in breast cancer initiation and progression. This has led to significant progress in developing and understanding human epidermal growth factor receptor 2 (HER2)-targeted therapies, which in turn, has translated into significant increases in median survival for patients with HER2-overexpressing breast cancer. It is becoming increasingly difficult to make specific recommendations for the optimal treatment of HER2-overexpressing breast cancer since the field is evolving so rapidly. However, despite the many randomized trials that have been undertaken showing improvement in survival, the current standard treatment for HER2-overexpressing breast cancer continues to revolve around the addition of chemotherapy to a HER2-targeted agent, which in turn, carries substantial toxicities. This article reviews agents that have recently been investigated to treat HER2-overexpressing breast cancers. The goal is ultimately to increase the magnitude and duration of response to trastuzumab-based treatment while minimizing toxicity. Studies addressing length of therapy duration, the superiority and side-effect profile of the different biological drug combinations, and determination of biomarkers of resistance to HER2 therapy will be instrumental in decreasing morbidity and mortality for patients with HER2-overexpressing breast cancer.